The influence of home and environmental characteristics on 5–18 years old children's health during the COVID-19 pandemic: A cross-sectional study in Iran - Golzarpour, Majid; Santana, Paula; Sajjadi, Homeira; Ghaed Amini Harouni, Gholamreza; Costa, Claudia; Ziapour, Arash; Azizi, Seyed Amar; Akbari, Mehdi; Afrashteh, Sima (Frontiers in Public Health, 2023)
Background The coronavirus disease (COVID-19) pandemic has dramatically changed the health and wellbeing of children. Therefore, this study aimed to investigate the relationship between the home environment and the environmental characteristics on 5–18 years old children health in Iran. Method An online survey was conducted among parents of children aged 5 to 18 living in large cities in Iran in 2021. The statistical population of this cross-sectional study was 500 people. In this survey, questionnaires on the quality of the home environment, exterior and interior landscapes of homes, and the Child Health Questionnaire (CHQ) were used to investigate the relationship between the home environment and environmental characteristics on 5–18 years old children health during the COVID-19 pandemic. The t-test and analysis of variance were used in SPSS 24, and the structural equation modeling (SEM) was utilized in AMOS 24 for analyzing the data. Results The average age of respondents was 37.13 ± 7.20, and that of children was 11.57 ± 3.47. 73.02% of the families were covered by insurance, and 74.08% of them lived in the metropolis. In addition, 65.04% of the families complied with the restrictions of the quarantine period. A share of 31% of the families live in villas, and 55% paid more attention to cleaning their homes during the COVID-19 pandemic than before. A positive and significant statistical relationship (β = 0.414, p < 0.001) was observed between the residence environment and child health. Thus, explained 17.5% of variations in child health. Conclusion The results showed that the children who lived in homes with an exterior landscape in nature had better health. In addition, the 5–18 years old children whose home landscape was a garden, compared to the other two groups (yard, balcony), had better health. Gardens are a potential source of health and not necessarily replaced by other natural environments, thus providing them along with green space is one of the crucial issues that should be considered.